2022
DOI: 10.1371/journal.pone.0279300
|View full text |Cite
|
Sign up to set email alerts
|

Predictive simulation of sit-to-stand based on reflexive-controllers

Abstract: Sit-to-stand can be defined as a set of movements that allow humans to rise from a sitting position to a bipedal standing pose. These movements, often categorized as four distinct kinematic phases, must be coordinated for assuring personal autonomy and can be compromised by ageing or physical impairments. To solve this, rehabilitation techniques and assistive devices demand proper description of the principles that lead to the correct completion of this motor task. While the muscular dynamics of the sit-to-sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 32 publications
(56 reference statements)
5
11
0
Order By: Relevance
“…We found that a 2-phase reflex based neural controller can realistically simulate the task of standing up (38), which is in line with Munoz et al (2022) (14) planar sit-to-stand simulation, and is different from the commonly reported 4-phase kinematic phases (37). In our model, the transition time is part of the optimization.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…We found that a 2-phase reflex based neural controller can realistically simulate the task of standing up (38), which is in line with Munoz et al (2022) (14) planar sit-to-stand simulation, and is different from the commonly reported 4-phase kinematic phases (37). In our model, the transition time is part of the optimization.…”
Section: Discussionsupporting
confidence: 84%
“…In the development of the sit-to-walk controller, we have tested several combinations of controllers, using muscle-reflex controllers and existing gait controllers (12). The most realistic and stable controller was a combination of two reflex-controllers, which is in line with what other research groups found for the sit-to-stand movement (14), followed by gait control.…”
Section: Methodssupporting
confidence: 88%
See 3 more Smart Citations